Budget Advocacy for Child Rights in the Philippines: How Civil Society Can Increase Public Spending for Child Rights - Leeuwen, Teun van (Student Undergraduate Research E-journal!, 2017)
Policy advocates for child rights work around the world on their mission to realize child rights for all children. In recent times, policy advocates have realized that important policies are often inadequately funded. Policy advocacy must be complimented with budget advocacy which targets the national budget. Budget advocacy is complex and has, therefore, not been widely adopted by advocates. This is an impactful problem. This thesis discusses state of the art budget advocacy literature and outlines the approaches used by experienced budget advocates. It provides key knowledge which allows the Child Rights Coalition Asia to draft concrete budget advocacy plans.